Increased incidence of malignancy in dermatitis herpetiformis. Issue 6358 (1st January 1983) - Leonard, J N; Tucker, W F; Fry, J S; Coulter, C A; Boylston, A W; McMinn, R M; Haffenden, G P; Swain, A F; Fry, L
Abstract : A retrospective study of 109 patients with dermatitis herpetiformis showed that malignant tumours had developed in seven patients, the expected incidence being 2.93, giving a relative risk of 2.38. In three of the seven patients the malignancy was a lymphoma, giving a relative risk of 100 for this tumour (expected incidence 0.03). In six of the seven patients who developed malignancies small-intestinal biopsy specimens were macroscopically abnormal, giving a relative risk of 4.22 in this group, which is similar to that reported in adult coeliac disease. Patients treated with a gluten-free diet appeared to have a reduced risk of developing malignancy compared with those taking a normal diet (relative risk with gluten-free diet 1.01 and with normal diet 3.09). A small subgroup of eight patients with linear IgA dermatitis herpetiformis were also studied: three developed malignant disease and in one the tumour was a lymphoma.